PEMBELAJARAN JARAK JAUH TUTUR DAN TINDAKAN TOKOH TEKS FIKSI BAHASA INDONESIA KELAS VI DI SDN 211 BABAKAN PRIANGAN DALAM MASA PANDEMI COVID-19 - Deni Suwardi Sopandi; Jajang Bayu Kelana (IKIP Siliwangi, 2021)
This study aims to determine the distance learning of the speech and actions of the 6th-grade Indonesian fictional text characters at SDN 211 Babakan Priangan during the Covid-19 pandemic. The research method used is descriptive qualitative. The subjects in this study were students of class VI SDN 211 Babakan Priangan. The instruments used were a description sheet and a questionnaire. As a result, distance learning can be used as an alternative in learning the speech and actions of Indonesian fictional text characters.